PENINGKATAN KETERAMPILAN PERANCANGAN DAN PEMBUATAN RAK POT BUNGA MINIMALIS BERBAHAN BESI NAKO BAGI SISWA SEKOLAH MENENGAH KEJURUAN NEGERI (SMKN) 7 TANGERANG BANTEN - I Wayan Sukania; Agni Purnamasiwi; Cidy Paramitha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Plants are the number one air filter because they are very effective at absorbing formaldehyde and many other functions. Likewise for the existence of plants in the environment of SMKN 7 Tangerang. However, the condition of the plants around the school area is felt to be very poor both in number and arrangement. The use of flower pot racks to place flower pots allows the arrangement of plants in a vertical direction and arrangement in certain configurations. This PKM activity was carried out at SMKN 7 Tangerang. Based on information from the academic section, it is known that the provision of product design theory and practical experience of welding for students is still lacking. Therefore, the practice of designing plant pot racks and the practice of making flower pot racks directly with the welding process is welcomed. PKM activities are carried out in 2 stages. The first stage produces various aesthetic minimalist plant pot rack concepts and meets certain set criteria. The next stage is the practice of realizing the selected design. The work to realize the product is measuring materials, cutting, sanding, grinding, assembling, drilling, painting and finishing. PKM questionnaires are given at the beginning and end of the activity to find out the amount of addition to the knowledge, skills and insights of the participants. PKM activities have produced functional, minimalist and aesthetic flower pot rack concepts and prototypes. PKM activities are able to increase knowledge and understanding of the stages of designing and developing a commercial product by 69%. Practical activities in the welding workshop were able to increase the knowledge and understanding of all participants on how to use welding machines, saws, drills, grinders and other supporting equipment used in welding workshops. All participants were satisfied with the materials and methods of this PKM activity.